1998
DOI: 10.1172/jci3234
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-driven clonal proliferation of B cells within the target tissue of an autoimmune disease. The salivary glands of patients with Sjögren's syndrome.

Abstract: Structures resembling germinal centers are seen in the salivary glands of patients with Sjögren's syndrome, but it is not known whether the microenvironment of these cell clusters is sufficient for the induction of a germinal center response. Therefore, we cloned and sequenced rearranged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
286
1
34

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(350 citation statements)
references
References 43 publications
29
286
1
34
Order By: Relevance
“…Some of the studies we found [10,12,14] contained lineage trees but no published sequences. In others, only sequences were published [16][17][18][19][20][21]; in these cases, germline genes were identified by alignment with published human IGV using DNAPLOT (http://vbase.mrc-cpe.cam.ac.uk/), and accordingly grouped and aligned using ClustalW (http://www.ebi.ac.uk/clustalw/).…”
Section: Lineage Tree Generation and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the studies we found [10,12,14] contained lineage trees but no published sequences. In others, only sequences were published [16][17][18][19][20][21]; in these cases, germline genes were identified by alignment with published human IGV using DNAPLOT (http://vbase.mrc-cpe.cam.ac.uk/), and accordingly grouped and aligned using ClustalW (http://www.ebi.ac.uk/clustalw/).…”
Section: Lineage Tree Generation and Measurementsmentioning
confidence: 99%
“…Mutational lineage trees of B cell clones from patients with MG, RA, SS, and MS [6,[16][17][18][19][20][21], and from normal human GCs [25][26], were created from published and unpublished IgV sequence data; we also used published lineage trees [12,10,14]. Each dataset contained IGV sequences from different IGV groups and patients (Table 1).…”
Section: Large Variability Of Ai Data Sets and The Necessity For Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphoid infiltrates within the inflamed glands often contain germinal center (GC)-like structures consisting of T and B cell aggregates with proliferating lymphocytes and a network of follicular dendritic cells and activated endothelial cells (3,4). Besides antigen-driven clonal proliferation of B cells (3,5), analyses of inflamed glandular tissue from patients with primary SS also reveal a polyclonal accumulation of CD27ϩ memory B cells and CD27 high plasma cells (6,7). Moreover, immunophenotyping studies indicate that there is disturbed B cell homeostasis in patients with primary SS, with diminished frequencies and absolute numbers of peripheral CD27ϩ memory B cells (6,8,9).…”
mentioning
confidence: 99%
“…20 Functional antigen-driven B-cell follicle-like structures with germinal centres and numerous plasma cells are found in the target tissues of autoimmune diseases such as the salivary glands of Sjö gren's syndrome, rheumatoid synovial membranes, and thyroid glands from patients with Hashimoto's thyroiditis and Grave's disease. 21,22 B cells have many potential key roles in the pathogenesis of autoimmune diseases. It has recently been proposed that B lymphocytes may play a more critical role in the induction of immunological activities as an antigenpresenting cell population, and that they are essential for the initial development and/or activation of autoreactive T cells in rheumatoid arthritis.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%